Rethinking Education and Livelihoods in India. (January 2022) - Endow, Tanuka; Mehta, Balwant Singh
The COVID-19 crisis has revealed a need for rethinking approaches to education and livelihoods. Education in its present dispensation does not provide equitable access to children from marginalized segments of the population. It also suffers from deficits in the areas of social and emotional skills, over-emphasis on the three Rs, language used as a medium of instruction, and excessive competition for scoring marks, among others. There is very low uptake of vocational education. The National Education Policy 2020 tries to address some of these issues and plans on closer integration of vocational education with the school framework. High unemployment rates of educated youth, along with underemployment due to skill mismatch, show poor school-to-work transition and underscore the importance of TVET for youth in the future. Skill already exists in the economy in informal knowledge systems which are largely undocumented and thus not acknowledged in the formal system. These need to be combined with Western-centric knowledge systems so that the imbalance between formally educated/trained workers and informally trained workers is redressed. There is also a need to bring back the joy of learning, as Tagore's experimentation with education has demonstrated.